Perbandingan Recovery Aktif dengan Recovery Pasif terhadap Tingkat Penurunan Asam Laktat dan Denyut Nadi Setelah Latihan Intensif Atlet Bulutangkis UKM UPI - Subekti, Robbi Radhiya; Mulyana, Boyke; Nida'ul (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2026)
This study aimed to analyze the differences in effectiveness between active recovery and passive recovery on changes in blood lactate levels and heart rate after high-intensity exercise among badminton athletes of the UKM at Universitas Pendidikan Indonesia (UPI). High-intensity exercise can induce physiological fatigue, which is reflected in changes in blood lactate concentration and increased heart rate, thereby requiring appropriate recovery methods to support athletes’ recovery processes. This research employed a quantitative approach using a quasi-experimental two-group pretest–posttest design. The sample consisted of 20 badminton athletes of the UPI Student Activity Unit, who were divided into an active recovery group and a passive recovery group. Blood lactate levels were measured using a lactate analyzer, while heart rate was measured using an oximeter. Data were analyzed using the Wilcoxon test and the Mann–Whitney U test according to the data distribution. The results showed a significant change in blood lactate levels in the passive recovery group (p = 0.007), whereas the active recovery group did not show a significant change (p = 0.059). For heart rate, the Mann–Whitney U test indicated a significant difference between the active recovery and passive recovery groups (p = 0.049), with passive recovery demonstrating more optimal heart rate changes compared to active recovery. These findings indicate that passive recovery provides a more favorable physiological recovery response than active recovery following high-intensity exercise among badminton athletes of the UKM UPI.